Radiolabeled Somatostatin Analogue Therapy Of Gastroenteropancreatic Cancer - Bodei, Lisa; Kwekkeboom, Dik J.; Kidd, Mark; Modlin, Irvin M.; Krenning, Eric P. (Seminars in nuclear medicine, 2016)
Peptide receptor radionuclide therapy (PRRT) has been utilized for more than two decades and has been accepted as an effective therapeutic modality in the treatment of inoperable or metastatic gastroenteropancreatic neuroendocrine neoplasms (NENs) or neuroendocrine tumors (NETs). The two most commonly used radiopeptides for PRRT, 90Y-octreotide and 177Lu-octreotate, produce disease-control rates of 68%-94%, with progression-free survival rates that compare favorably with chemotherapy, somatostatin analogues, and newer targeted therapies. In addition, biochemical and symptomatic responses are commonly observed. In general, PRRT is well tolerated with only low to moderate toxicity in most individuals. In line with the need to place PRRT in the therapeutic sequence of gastroenteropancreatic NENs, a recently sponsored phase III randomized trial in small intestine NENs treated with 177Lu-octreotate vs high-dose octreotide long-acting release demonstrated that 177Lu-octreotate significantly improved progression-free survival. Other strategies that are presently being developed include combinations with targeted therapies or chemotherapy, intra-arterial PRRT, and salvage treatments. Sophisticated molecular tools need to be incorporated into the management strategy to more effectively define therapeutic efficacy and for an early identification of adverse events. The strategy of randomized controlled trials is a key issue to standardize the treatment and establish the position of PRRT in the therapeutic algorithm of NENs.